Children's Facial Trustworthiness Judgments: Agreement and Relationship with Facial Attractiveness - Ma, Fengling; Xu, Fen; Luo, Xianming (Frontiers in Psychology, 2016)
This study examined developmental changes in children’s abilities to make trustworthiness judgements based on faces and the relationship between a child’s perception of trustworthiness and facial attractiveness. One hundred and one 8-, 10- and 12-year-olds, along with 37 undergraduates, were asked to judge the trustworthiness of 200 faces. Next, they issued facial attractiveness judgements. The results indicated that children made consistent trustworthiness and attractiveness judgements based on facial appearance, but with-adult and within-age agreement levels of facial judgements increased with age. Additionally, the agreement levels of judgements made by girls were higher than those by boys. Furthermore, the relationship between trustworthiness and attractiveness judgements increased with age, and the relationship between two judgements made by girls was closer than those by boys. These findings suggest that face-based trait judgement ability develops throughout childhood and that, like adults, children may use facial attractiveness as a heuristic cue that signals a stranger’s trustworthiness.